A frame-supported ultrathin electrospun polymer membrane for transplantation of retinal pigment epithelial cells. (12th August 2015) - Popelka, Štěpán; Studenovská, Hana; Abelová, Lucie; Ardan, Taras; Studený, Pavel; Straňák, Zbyněk; Klíma, Jiří; Dvořánková, Barbora; Kotek, Jiří; Hodan, Jiří; Rypáček, František
Abstract: We report on the design and fabrication of a frame-supported nanofibrous membrane for the transplantation of retinal pigment epithelial (RPE) cells, which is a promising therapeutic option for the treatment of degenerative retinal disorders. The membranous cell carrier prepared from 640 nm-thick poly(DL-lactide) fibres uniquely combines high porosity, large pore size and low thickness, to maximize the nutrient supply to the transplanted cells in the subretinal space and thus to enhance the therapeutic effect of the transplantation. The carrier was prepared by electrospinning, which made it easy to embed a 95 μ m-thick circular supporting frame 2 mm in diameter. Implantations into enucleated porcine eyes showed that the frame enabled the ultrathin membrane to be handled without irreversible folding, and allowed the membrane to regain its flat shape when inserted into the subretinal space. We further demonstrated that the minimum membrane thickness compatible with the surgical procedure and instrumentation employed here was as low as 4 μ m. Primary porcine RPE cells cultivated on the membranes formed a confluent monolayer, expressed RPE-specific differentiation markers and showed transepithelial resistance close to that of the native RPE. Most importantly, the majority of the RPE cells transplanted into the subretinal space remained viable. The ultrathin, highly porous, and surgically convenient cell carrier presented here has the potential to improve the integration and the functionality of transplanted RPE cells.